2020
DOI: 10.1111/acel.13259
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian stiffness increases with age in the mammalian ovary and depends on collagen and hyaluronan matrices

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
119
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(164 citation statements)
references
References 46 publications
14
119
1
Order By: Relevance
“…Recently, Tanaka et al analyzed plasma proteins of all age groups and identified ~650 age-associated proteins in which extracellular matrix-related proteins were enriched [ 67 ]. Another recent study demonstrated that abundance of hyaluronan, an ECM glycosaminoglycan, gradually decreased with age, leading to the alteration in biomechanical properties of ECM [ 68 ]. As a critical factor for skin moisture, hyaluronan preserves the hydration of skin, thereby suppresses skin aging.…”
Section: Molecular Profile Changes With Age In the Periodontiummentioning
confidence: 99%
“…Recently, Tanaka et al analyzed plasma proteins of all age groups and identified ~650 age-associated proteins in which extracellular matrix-related proteins were enriched [ 67 ]. Another recent study demonstrated that abundance of hyaluronan, an ECM glycosaminoglycan, gradually decreased with age, leading to the alteration in biomechanical properties of ECM [ 68 ]. As a critical factor for skin moisture, hyaluronan preserves the hydration of skin, thereby suppresses skin aging.…”
Section: Molecular Profile Changes With Age In the Periodontiummentioning
confidence: 99%
“…In this study, we demonstrated, to our knowledge, the first non-invasive mechanical mapping, with micron-level spatial resolution, of ovarian mechanics in situ. From a biological perspective, our work represents a first step towards addressing the mechanical aspects of folliculogenesis, which has gained recognition due to emerging evidence that mechanical stress in the ovary can influence the quality of the growing oocytes through ECM stiffness 40,41 , Hippo signalling pathway 42,43 and increased fibrosis 44,45 .…”
Section: Discussionmentioning
confidence: 99%
“…3). This may be due to the fact that the theca cells are associated with increased expression of hyaluronic acid, which is known to promote tissue hydration 45 . The theca cell layer therefore provides a softer microenvironment that may serve as a mechanical 'sponge' to buffer the oocyte and somatic cells against external mechanical stress through stress dissipation.…”
Section: Discussionmentioning
confidence: 99%
“…An important component of the stromal compartment is the ECM and, in particular, its ubiquitous component, hyaluronan; a linear polysaccharide with pleiotropic roles in tissue structure, cell signaling and inflammation (Rowley et al, 2020;Takasugi et al, 2020). In the context of the ovary, recent work has demonstrated that total hyaluronan content in the ovarian stroma decreases with age and is effectively "replaced" by collagen leading to dramatic changes in ovarian biomechanics pertaining to increased stiffness (Amargant et al, 2020). Importantly, these age-associated changes are conserved between the mouse and humans (Amargant et al, 2020) and may be associated with the production of oocytes with compromised morphology, poor meiotic competence, and impaired granulosa cell function (Amargant et al, 2020;Rowley et al, 2020).…”
Section: Ovarian Tissue Aging and Reproductive Disordersmentioning
confidence: 99%
“…In the context of the ovary, recent work has demonstrated that total hyaluronan content in the ovarian stroma decreases with age and is effectively "replaced" by collagen leading to dramatic changes in ovarian biomechanics pertaining to increased stiffness (Amargant et al, 2020). Importantly, these age-associated changes are conserved between the mouse and humans (Amargant et al, 2020) and may be associated with the production of oocytes with compromised morphology, poor meiotic competence, and impaired granulosa cell function (Amargant et al, 2020;Rowley et al, 2020). In pathological states or during tissue aging, it also known that the fragmentation of hyaluronan yields a low molecular weight polymer (<250 kDa) linked to inflammation, fibrotic disease (Takasugi et al, 2020).…”
Section: Ovarian Tissue Aging and Reproductive Disordersmentioning
confidence: 99%